Blok Aksilar dengan Panduan Ultrasonografi pada Operasi Debridement Lengan Bawah Pasien Systemic Lupus Erythematosus, Gagal Ginjal Kronik, Sirosis Hepatis, dan Gagal Jantung - Mohamad Andy Prihartono; Dedi Fitri Yadi; Erwin Pradian (Jurnal Anestesi Perioperatif, 2013)
Axillary block is beneficial when applied to a forearm operation. A 28-year-old female patient diagnosed with systemic lupus erythematosus, chronic renal failure, hepatic cirrhosis and heart failure, was planned for necrotomy debridement operation of the forearm in Dr. Hasan Sadikin Hospital-Bandung in March 2012. An axillary block anesthesia was done with Sonosite M Turbo ultrasound guidance that used high frequency linear probe, 50 mm stimulating needle, and nerve stimulator containing bupivacaine 0.5% and epinephrine adjuvant 1:200,000. The operation can be initiated after the block was achieved and the duration of operation was 1 hour. In conclusions, axillary block with ultrasound guidance gives satisfying result with higher success rate. Peripheral nerve block (regional anesthesia) is more beneficial to this patient than general anesthesia due to multiple complications.